FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA - STEVEN STEVEN; HARYO SUPARMUN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this study is to investigate the effect of managerial ownership, institutional ownership, foreign ownership, concentrated ownership, dividend policy, firm size, liquidity, financial performance and capital structure toward firm value. This used 30 listed non-financial companies in Indonesia Stock Exchange for year2014-2016. Sampling method used is purposive sampling and data analysis model used is multiple regression analysis. The results of this study indicate that institutional ownership, financial performance and capital structure have a positive and significant influence on firm value. Managerial ownership, foreign ownership, concentrated ownership, dividen policy, firm size and liquidity do not have significant effect on firm value.